Clostridium difficile : incidência da infecção e caracterização das cepas isoladas de pacientes com diarreia internados em um hospital oncológico de Fortaleza, Ceará - Costa, Cecília Leite (2014)
Clostridium difficile is a strictly anaerobic, spore-forming, toxin-producing Gram positive bacillus. Currently, it is the main cause of nosocomial diarrhea associated with antibiotic use. Cancer patients are a major risk group for C. difficile infection (CDI), since the use of chemotherapeutic agents can alter the intestinal mucosa. Furthermore, these patients are often immunosuppressed and often use broad spectrum antibiotics. Considering the pathogenicity of C. difficile and the importance of this infection in hospitalized patients, this study aimed to determine the incidence and the phenotypical and genotypical characterization of strains of C. difficile isolated from cancer patients at Haroldo Juaçaba Hospital, Fortaleza, Ceará. During the 12 month period (May/2013 to May/2014) 41 diarrheic fecal samples were collected. Toxins A/B were detected from feces through a commercial ELISA detection kit. Then, the samples were cultivated on cefoxitine-cycloserine-frutose agar (CCFA) and incubated anaerobically. Isolates were submitted to several analyses, including phenotypical identification, detection of toxin genes and of a fragment of the tpi gene (definitive identification) by conventional PCR. The susceptibility of the strains to 12 antimicrobial agents was determined by E-test. Genotyping of the strains was also performed through molecular PFGE analysis. Out of 41 samples, 46.3% (19/41) were positive for either one or both of the performed tests: detection of toxin A/B and/or culture of C. difficile. C. difficile was recovered from three samples (15.8% - 3/19). The tpi, tcdA and tcdB genes were detected in all of the isolates. The binding domain of the binary toxin (cdtB) was not detected as well as no deletions were observed in the tcdC gene of the analysed isolates. All strains belonged to the same genotype, NAP4. Regarding the antimicrobial susceptibility of the strains, resistance to two or more antibiotics (azithromycin, tetracycline, ciprofloxacin, levofloxacin, ceftriaxone and cefotaxime) was observed. Out of the 19 positive patients, 57.9% (11/19) were using antibiotics and under chemotherapy. This paper describes the incidence of CDI in patients with cancer, and shows for the first time the detection of community-associated Clostridium difficile infection (CA-CDI) in those patients in Brazil, highlighting the importance of studying this bacterium for understanding the epidemiological situation of this infection and its spread among Brazilian hospitals.